Herpes Simplex Virus Infections in Preterm Infants - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2007)
A retrospective review of herpes simplex virus (HSV) infections within the first 30 days after birth in infants born at <37 weeks was conducted at Johns Hopkins University School of Medicine, Baltimore, MD.